PENILAIAN RISIKO KECELAKAAN KERJA PADA TENAGA KERJA BONGKAR MUAT DI PELABUHAN TELUK NIBUNG TANJUNG BALAI ASAHAN TAHUN 2015 - wahana saragih; eka lestari mahyuni; arfah mardiyah lubis (Lingkungan dan Kesehatan Kerja, 2015)
ABSTRACT Unloading and loading is a job that need physical activity to lift and haul goods. This job have hazard potensial for work accident and health problems. Therefore, the objective of this research is to assess the hazard of unloading and loading workers at Teluk Nibung Port Tanjung Balai, Asahan. The research was a descriptive survey. The data of work accident and health problems hazard in workers were gathered by HIRA method.The Object of the research was to identify the process in stevedoring, cargoding, and delivery. The result of research in unloading and loading workers at stevedoring showed that the highest hazard were found at worker who opened the boat cover and moved goods from boat to darmaga. In cargoding, the highest hazard were found in low back pain risk at worker and hit when workers bring and stack goods in warehouse. In delivery, the highest hazard was found in worker work in truck machine. The results show the value of the highest risk from the analysis of risk is high with the potential for accidents such as drowning, was hit and fell. The recommended that the cooperative workers unloading create safety signs and provide personal protective equipment to minimize risks. Keyword : Unloading and loading, risk assessment